Regional to global correlation of Eocene–Oligocene boundary transition successions using biostratigraphic, geophysical and geochemical methods. (12th July 2019) - Ellwood, Brooks B.; Febo, Lawrence; Anderson, Laurie; Hackworth, Rebecca T.; Means, Guy H.; Bryan, Jonathon A.; Tomkin, Jonathan; Rowe, Harry; Jovane, Luigi
Abstract: Regional to global high-resolution correlation and timing is critical when attempting to answer important geological questions, such as the greenhouse to icehouse transition that occurred during the Eocene–Oligocene boundary transition. Timing of these events on a global scale can only be answered using correlation among many sections, and multiple correlation proxies, including biostratigraphy, lithostratigraphy, geochemistry and geophysical methods. Here we present litho- and biostratigraphy for five successions located in the southeastern USA. To broaden the scope of correlation, we also employ carbon and oxygen stable isotope and magnetic susceptibility (χ) data to interpret these sections regionally, and correlate to the Global Boundary Stratotype Section and Point (GSSP) near Massignano in central Italy. Our results indicate that approaching the Eocene–Oligocene boundary, climate warmed slightly, but then δ 18 O data exhibit an abrupt c. +5 ‰ positive shift towards cooling that reached a maximum c. 1 m below the boundary at St Stephens Quarry, Alabama. This shift was accompanied by a c. −3 ‰ negative shift in δ 13 C interpreted to indicate environmental changes associated with the onset of the Eocene–Oligocene boundary planktonic foraminiferal extinction event. The observed cold pulse may be responsible for the final extinction of Hantkeninidae, used to define the beginning of the Rupelian Stage. Immediately preceding the boundary, Hantkeninidae species dropped significantly in abundance and size (pre-extinction dwarfing occurring before the final Eocene–Oligocene extinctions), and these changes may be the reason for inconsistencies in past Eocene–Oligocene boundary placement in the southeastern USA.